A Homotopy Algorithm for Solving the Inverse Eigenvalue Problem for Complex Symmetric Matrices (Journal of Computational Mathematics, 2018)
A homotopy algorithm for solving the inverse eigenvalue problem for complex symmetric matrices is suggested. Some numerical examples are presented.